Introduction to the special issue "Mobilising queer joy: establishing queer joy studies" - Wright, JJ (Jessica); Burkholder, Casey (My University, 2025)
Our introduction to the special issue “Mobilising Queer Joy” reflects an urgent need for queer joy studies amidst a sociopolitical climate that feels increasingly ruinous. We reject the ‘joy deficit’ in sociological research that fixates on homogenous, misery-filled visions of 2SLGBTQIA+ existence, and which is severed from the profound beauty of queer love, queer and trans joy, gender euphoria, and the strength and depth of 2SLGBTQIA+ community care and chosen families. In addition to introducing the six articles in the special issue from authors in Canada, the Philippines, Australia, and the US, we aim to establish queer joy studies by articulating the affective power of queer joy for collective resistance and social transformation. Queer joy is more than a kitschy slogan on a tote bag or splashed on the side of a big bank’s Pride float; it is a collective experience that allows us to feel more alive and connected to our personal capacities and power. The queer joy we are interested in is dangerous to empire and colonial powers. It does not deny the relationship with ambivalence, rage, and grief, and instead mobilises these affects to confront injustices in our existing social order. Some of the questions we ask include: How does queer joy act as world-making and dream mapping of new, more sustainable futures? How might we further theorize and mobilise queer joy as a disruption to settler colonial, carceral logics? How might the transformative power of queer joy be amplified to fragment and challenge the rise of fascism and populism that seeks to exterminate it?
Keywords: Mobilising Queer Joy; queer joy studies; collective resistance; social transformation